Research Bibliography—Stochastic Dominance: A Research Bibliography - Bawa, Vijay S. (Management Science, 1982)
About 400 publications, working papers and books are included in this bibliography on Stochastic Dominance. It contains an exhaustive listing of papers that are either basic contributions to this subject or primarily concerned with applications of the Stochastic Dominance concepts. It also contains selective listing of papers from finance, economics, mathematics, mathematical physics, mathematical psychology, operations research and statistics literature to illustrate the wide applicability of Stochastic Dominance concepts.